Proses Pengimbuhan Dalam Bahasa Berawan: Satu Kajian Morfologi - Vallenfield California Anak Lau, Vallenfield California Anak Lau (Universiti Malaysia Sarawak (UNIMAS), 2025)
This study compares the affixation process between the Berawan language and Standard Malay. The focus is on the types of affixes in the Berawan language, such as prefixes, suffixes, circumfixes, and infixes, as well as their comparison with equivalent forms and functions in Standard Malay. This research adopts a descriptive qualitative research design, with data collected through interviews with five native Berawan speakers in Kampung Loagan Bunut, Tinjar Baram. The data were analysed using content analysis methods based on the framework of Tatabahasa Dewan (Third Edition). Findings indicate that although there are similarities in the types of affixes used, the Berawan language possesses unique affixation characteristics that differ in terms of structure and usage. This study is expected to contribute to the linguistic documentation of the Berawan language as a threatened ethnic language and serve as a foundation for efforts in cultural heritage preservation and further research in the field of ethnic language morphology in Malaysia.